Sustained viral response and treatment‐induced cytopenia correlate with SLCs and KLF12 genotypes in interferon/ribavirin‐treated Chinese chronic hepatitis C patients. Issue 8 (August 2016) - Mei, Ruqi; Chi, Xiumei; Wu, Ruihong; Xu, Hongqin; Wang, Xiaomei; Gao, Xiuzhu; Sun, Haibo; Lv, Juan; Yu, Ge; Kong, Fei; Jiang, Jing; Sun, Bing; et al.
Abstract: Background and aim: Genetic variations in solute carrier (SLC) genes are associated with liver diseases, and Kruppel‐like factor 12 (KLF12) affects the b chain of hemoglobin. We investigated possible correlations of SLC and KLF12 polymorphisms with viral clearance (spontaneous and treatment‐induced) and adverse effects in Chinese chronic hepatitis C (CHC) patients. Methods: We genotyped the single nucleotide polymorphisms in 525 CHC patients, 137 patients with spontaneous clearance, and 207 healthy controls. Three hundred fifty‐seven CHC patients received recombinant interferon‐alpha2b/ribavirin (IFN‐α2b/RBV) treatment, and 175 patients were chosen for analysis of drug‐induced cytopenia. All raw P ‐values were corrected by the Bonferroni method. Results: A higher rate of sustained viral response was detected in patients with SLC4A11 rs3810560 CC variant versus TT/TC variant (76.9% vs 59.2%; OR, 2.42; 95% CI, 1.06–5.56, P = 0.037 after adjustment), but there was no significant difference among different hepatitis C virus genotypes. RBV‐induced anemia was independently correlated with SLC29A1 rs760370 AA genotype (OR, 2.90; 95% CI, 1.29–6.54, P = 0.010), and the severity of IFN‐induced thrombocytopenia was related to GG genotype (OR, 4.98; 95% CI, 1.27–19.61; P = 0.021); the detected effects held true for HCV‐2a patients but weakened in HCV‐1b patients. A reactive increase in platelet count was closely associated with KLF12 rs9543524 TT variant. Conclusion: SLC4A11 rs3810560 polymorphism independently affected the sustained viral response rates in CHC patients, whereas SLC29A1 rs760370 and KLF12 rs9543524 single nucleotide polymorphisms correlated with treatment‐induced adverse events. Clearly, the predictive power varied with HCV genotypes and the reason for genotype‐dependent discrepancy was not fully understood.